Opposition in Novel Titir Dedes : Prayer And Curse Work Amalia Jonah : Analysis Julia Kristeva's Intertextuality - Chelsa Aura Diva Unzilla Gunawan (Jurnal Pengetahuan dan Pendidikan, 2025)
This study aims to explore and identify the oppositions present in the novel Tutur Dedes: Prayers and Curses by Amalia Yunus. The analysis is grounded in Julia Kristeva’s theory of intertextuality, which emphasizes the relationships between texts and the ways in which meanings are shaped through these connections. By employing a library research approach and utilizing descriptive qualitative methods, the study systematically examines the textual elements to reveal contrasting themes and ideas embedded within the narrative. The analysis identifies key oppositions, notably the conflict between the War of Ganter and the depiction of the female knight. These oppositions highlight the complex portrayal of women in the novel, illustrating them as empowered agents capable of making independent decisions and fully aware of their personal needs and desires. Furthermore, the novel demonstrates that women can exert significant influence on societal decisions and contribute to transformative changes within their communities. The findings underscore the novel’s contribution to literary discussions on gender, power, and social agency, revealing how intertextual connections reinforce the representation of women as autonomous and influential figures. This study contributes to a deeper understanding of how literary oppositions function to challenge traditional norms and expand the discourse on women’s roles in contemporary literature.